Canva in the Classroom: Insights into High School Students’ Views on its Role in Islamic Education - Astuti, Baida; Mahdalena, Mahdalena; Susianti, Memi (PPSDP International Journal of Education, 2024)
This study aims to examine high school students’ perceptions of Canva’s role in Islamic Education at SMA Negeri 5 Kepahiang. Using a mixed-method approach, the study collected quantitative data through a structured questionnaire and qualitative data through focus group discussions (FGDs) with 30 second-year students who have used Canva in their classes. Results indicate that Canva positively influences student engagement, comprehension, and ease of use in learning Islamic concepts. Most students found Canva helpful in making lessons more engaging and enhancing their understanding of abstract concepts through visual aids. The findings further reveal that Canva fosters creativity and collaboration, as students frequently utilized the platform’s features to design presentations and projects collaboratively. Additionally, teachers reported that Canva supported differentiated instruction by allowing personalized content delivery. The novelty of this study lies in its focus on Canva’s specific application in Islamic Education, a relatively under-explored area in digital learning tools research. The study contributes to educational practices by providing evidence that Canva can support and enrich learning experiences in religious education, suggesting potential for wider implementation in similar subjects.